Carbon nanotube aqueous dispersion, conductive film, electrode, and solar cell

The carbon nanotube water dispersion with specific solvent and dispersant properties addresses the issue of film strength in solar cells, enhancing conductivity and reliability by forming a stable conductive film with reduced defects.

JP7622642B2Active Publication Date: 2025-01-28ZEON CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021561319
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-28
Filing Date
2020-11-16
Publication Date
2025-01-28
Estimated Expiration
2040-11-16

AI Technical Summary

Technical Problem

Conventional methods for forming conductive films using carbon nanotubes in solar cells result in impaired film strength, leading to issues such as pinholes and peeling, which compromise the conversion efficiency and reliability of solar cells.

Method used

A carbon nanotube water dispersion is developed using a solvent system that includes non-proton-polar solvents, specific dispersants, and viscosity agents, which are easily dissolved or non-dissolved in the solvent, enhancing film strength and stability, thereby improving the conductivity and reliability of the conductive film.

Benefits of technology

The conductive film formed using this dispersion exhibits enhanced film strength, leading to improved conversion efficiency and reliability of solar cells, with reduced pinholes and peeling, ensuring long-term performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622642000003
    Figure 0007622642000003
  • Figure 0007622642000001
    Figure 0007622642000001
  • Figure 0007622642000002
    Figure 0007622642000002
Patent Text Reader

Abstract

The present invention provides a carbon nanotube aqueous dispersion capable of forming a conductive film that not only has excellent film strength but also allows a solar cell to exhibit high conversion efficiency and reliability. A carbon nanotube aqueous dispersion according to the present invention is a carbon nanotube aqueous dispersion for a solar cell electrode, said carbon nanotube aqueous dispersion being provided with an electrolytic solution containing an aprotic polar substance as a solvent. The carbon nanotube aqueous dispersion contains carbon nanotubes, a dispersant, a thickener, and water. The dispersant is soluble in the solvent. The thickener is insoluble in the solvent.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aqueous dispersion of carbon nanotubes, a conductive film, an electrode, and a solar cell. [Background technology]

[0002] Carbon nanotubes (hereinafter sometimes referred to as "CNTs") have various excellent properties such as electrical conductivity, thermal conductivity, and mechanical strength, and various industrial applications of CNTs have been considered. For example, focusing on their excellent electrical conductivity, technology for forming conductive films using CNTs has been considered.

[0003] A conductive film containing CNTs can be formed on a substrate by, for example, applying a carbon nanotube aqueous dispersion (hereinafter, sometimes referred to as a "CNT aqueous dispersion") containing CNTs, a dispersant, and water onto the substrate and drying it. The conductive film thus obtained is used to fabricate electrodes for solar cells such as dye-sensitized solar cells.

[0004] For example, in Patent Document 1, a first carbon layer is formed by applying a CNT aqueous dispersion onto a substrate and drying it, a second carbon layer is formed by applying a CNT aqueous dispersion onto the first carbon layer obtained and drying it, and the second carbon layer obtained is washed with water or the like to remove at least a part of the dispersant from the second carbon layer, thereby forming a conductive laminate having a conductive film. According to Patent Document 1, the conductive laminate obtained through the above steps has excellent conductivity because the dispersant, which is a resistance component, is removed by washing, and can exhibit excellent conversion efficiency in a dye-sensitized solar cell. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2015-146338 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, in the above conventional method, the strength of the conductive film is sometimes lost during cleaning, causing problems such as pinholes and peeling from the substrate. Even if an electrode having a conductive film with such lost strength is used, it is difficult to ensure that the solar cell fully exhibits excellent conversion efficiency and maintains the excellent conversion efficiency for a long period of time (i.e., ensures reliability).

[0007] Therefore, an object of the present invention is to provide an aqueous dispersion of carbon nanotubes capable of forming a conductive film having excellent film strength and capable of enabling a solar cell to exhibit excellent conversion efficiency and reliability. Another object of the present invention is to provide a conductive film that has excellent film strength and is capable of enabling a solar cell to exhibit excellent conversion efficiency and reliability. A further object of the present invention is to provide an electrode that can ensure the reliability of a solar cell while allowing the solar cell to exhibit excellent conversion efficiency. Another object of the present invention is to provide a solar cell that has excellent conversion efficiency and reliability. [Means for solving the problem]

[0008] The present inventor has conducted intensive research to achieve the above object. First, the present inventor has focused on the properties of a dispersant for aprotic polar substances used as a solvent in the electrolyte of a solar cell. The present inventor has focused on the fact that by using a dispersant that is easily soluble in aprotic polar substances used as a solvent in the electrolyte of a solar cell for preparing a CNT aqueous dispersion, the dispersant, which is a resistance component, can be dissolved in the electrolyte and removed from the conductive film without excessive washing (or washing itself) of the resulting conductive film. The present inventor has further conducted research and found that by adding a thickener that is difficult to dissolve in the aprotic polar substance used as the solvent to the CNT aqueous dispersion, the thickener can exert a binding ability in the conductive film incorporated inside the solar cell, suppressing detachment of the conductive film from the substrate, and improving the conversion efficiency and reliability of the solar cell, thereby completing the present invention.

[0009] That is, the present invention aims to advantageously solve the above problems, and the carbon nanotube aqueous dispersion of the present invention is a carbon nanotube aqueous dispersion for a solar cell electrode, comprising an electrolyte solution containing an aprotic polar substance as a solvent, and is characterized in that it contains carbon nanotubes, a dispersant, a thickener, and water, the dispersant being soluble in the solvent, and the thickener being insoluble in the solvent. By using a CNT aqueous dispersion in which CNTs and the dispersant and thickener having the above-mentioned specific properties are dissolved and / or dispersed in water, a conductive film with excellent film strength can be formed. And by using an electrode having the conductive film, the conversion efficiency and reliability of the solar cell can be improved.

[0010] In the present invention, a compound (dispersant, thickener) being "soluble" in a solvent (aprotic polar substance) means that it dissolves in the solvent at a concentration of 1% by mass at a temperature of 23°C (the insoluble portion cannot be visually confirmed), and "insoluble" means that it does not dissolve in the solvent at a concentration of 1% by mass at a temperature of 23°C even after stirring for 24 hours (the insoluble portion can be visually confirmed).

[0011] In the carbon nanotube aqueous dispersion of the present invention, the aprotic polar substance may be at least one selected from the group consisting of acetonitrile, γ-butyrolactone, 3-methoxypropionitrile, and triethylene glycol monomethyl ether.

[0012] In the carbon nanotube aqueous dispersion of the present invention, the dispersant and the thickener are preferably each made of a nonionic polymer. By using a nonionic polymer as the dispersant and also as the thickener, the strength of the conductive film can be further improved, and the conversion efficiency and reliability of the solar cell can be further increased.

[0013] In the carbon nanotube aqueous dispersion of the present invention, the dispersant is preferably a copolymer of styrene and methoxypolyethylene glycol methacrylate. By using a copolymer of styrene and methoxypolyethylene glycol methacrylate as the dispersant, the film strength of the conductive film can be further improved.

[0014] Furthermore, the present invention aims to advantageously solve the above problems, and the conductive film of the present invention is characterized in that it is obtained by using any one of the above-mentioned carbon nanotube aqueous dispersions. The conductive film formed from the above-mentioned CNT aqueous dispersion has excellent film strength. Furthermore, by producing an electrode using the conductive film, the conversion efficiency and reliability of a solar cell can be improved.

[0015] The present invention also aims to advantageously solve the above problems, and provides an electrode comprising the conductive film described above. The electrode comprising the conductive film described above can ensure the reliability of a solar cell while providing the solar cell with excellent conversion efficiency.

[0016] The present invention has an object to advantageously solve the above problems, and provides a solar cell comprising the above-mentioned electrode. A solar cell comprising the above-mentioned electrode has excellent conversion efficiency and reliability. Effect of the Invention

[0017] According to the present invention, it is possible to provide an aqueous dispersion of carbon nanotubes capable of forming a conductive film having excellent film strength and capable of enabling a solar cell to exhibit excellent conversion efficiency and reliability. Furthermore, according to the present invention, it is possible to provide a conductive film that has excellent film strength and is capable of enabling a solar cell to exhibit excellent conversion efficiency and reliability. Furthermore, according to the present invention, it is possible to provide an electrode that can ensure the reliability of a solar cell while allowing the solar cell to exhibit excellent conversion efficiency. Furthermore, according to the present invention, it is possible to provide a solar cell having excellent conversion efficiency and reliability. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a diagram showing a schematic configuration of an example of a dye-sensitized solar cell. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Here, the carbon nanotube aqueous dispersion of the present invention can be used for producing electrodes for solar cells, specifically, for forming a conductive film to be provided on the electrode. The conductive film of the present invention is formed using the carbon nanotube aqueous dispersion of the present invention. Furthermore, the electrode of the present invention comprises the conductive film of the present invention. And the solar cell of the present invention comprises the electrode of the present invention.

[0020] (Carbon nanotube water dispersion) The CNT aqueous dispersion of the present invention contains a dispersant, a thickener, and water as a solvent, and further contains other components as necessary. Here, the dispersant contained in the CNT aqueous dispersion of the present invention is characterized in that it is soluble in a solvent that is an aprotic polar substance contained in the electrolyte of a solar cell fabricated using an electrode having a conductive film formed from the CNT aqueous dispersion, and the thickener contained in the CNT aqueous dispersion of the present invention is characterized in that it is insoluble in the above-mentioned solvent. In other words, the dispersant is characterized in that the thickener is characterized in that it is soluble and the thickener is characterized in that it is insoluble, using the "solvent" that is an aprotic polar substance used in the electrolyte as the same standard.

[0021] Furthermore, by using the CNT aqueous dispersion of the present invention, it is possible to form a conductive film that has excellent film strength and is capable of enabling a solar cell to exhibit excellent conversion efficiency and reliability.

[0022] <Carbon nanotubes> The CNT is not particularly limited, and single-walled carbon nanotubes and / or multi-walled carbon nanotubes can be used. The CNT is preferably a single-walled to five-walled carbon nanotube, and more preferably a single-walled carbon nanotube. These may be used alone or in combination of two or more types. The fewer the number of walls of the carbon nanotube, the larger the specific surface area becomes even with a small amount of blending, and the obtained conductive film can be given properties such as catalytic activity when used in a solar cell electrode.

[0023] In addition, the average diameter of the CNT is preferably 1 nm or more, preferably 60 nm or less, more preferably 30 nm or less, and particularly preferably 10 nm or less. If the average diameter of the CNT is 1 nm or more, the dispersibility of the CNT can be improved, and properties such as electrical conductivity can be stably imparted to the conductive film. In addition, if the average diameter of the CNT is 60 nm or less, even with a small blending amount, properties such as catalytic activity when used in solar cell electrodes can be efficiently imparted to the obtained conductive film. In the present invention, the "average diameter of carbon nanotubes" can be determined by measuring the diameter (outer diameter) of, for example, 20 CNTs on a transmission electron microscope (TEM) image and calculating the number average value.

[0024] In addition, it is preferable to use CNTs having a ratio (3σ / Av) of the standard deviation of diameter (σ: sample standard deviation) multiplied by 3 to the average diameter (Av) of more than 0.20 and less than 0.80, more preferably more than 0.25, and particularly preferably more than 0.40. If CNTs having a 3σ / Av of more than 0.20 and less than 0.80 are used, the performance of the manufactured conductive film can be further improved. The average diameter (Av) and standard deviation (σ) of the CNTs may be adjusted by changing the production method or conditions for the CNTs, or by combining multiple types of CNTs obtained by different production methods.

[0025] The CNTs that are usually used are those that show a normal distribution when the diameter measured as described above is plotted on the horizontal axis and the frequency on the vertical axis and approximated with a Gaussian.

[0026] In addition, the average length of the CNT is preferably 10 μm or more, more preferably 50 μm or more, particularly preferably 80 μm or more, and preferably 600 μm or less, more preferably 500 μm or less, particularly preferably 400 μm or less. If the average length is 10 μm or more, a conductive path can be formed in the conductive film with a small amount of compounding, and the strength of the conductive film is high. If the average length is 600 μm or less, the coating property to the substrate can be improved when applying the dispersion. Therefore, if the average length of the CNT is within the above range, the surface resistivity of the conductive film can be sufficiently reduced and high catalytic activity can be imparted to the conductive film. In the present invention, the "average length of carbon nanotubes" can be determined by measuring the lengths of, for example, 20 CNTs on a scanning electron microscope (SEM) image and calculating the arithmetic average value.

[0027] Furthermore, CNTs usually have an aspect ratio of more than 10. The aspect ratio of CNTs can be determined by measuring the diameter and length of 100 randomly selected CNTs using a scanning electron microscope or a transmission electron microscope and calculating the average value of the ratio of diameter to length (length / diameter).

[0028] In addition, CNTs have a BET specific surface area of ​​200 m 2 / g or more, and 2 / g or more is more preferable, and 600m 2 / g or more is particularly preferable, and 2000m 2 / g or less, and 2 / g or less is more preferable, and 1600m 2 It is particularly preferable that the BET specific surface area of ​​the CNT is 200 m 2 / g or more, the dispersibility of the CNTs can be increased, and even with a small blending amount, the resulting conductive film can be imparted with properties such as electrical conductivity and catalytic activity when used in solar cell electrodes. 2 / g or less, the obtained conductive film can be imparted with properties such as electrical conductivity and catalytic activity when used in a solar cell electrode, and the coatability of the CNT aqueous dispersion can be stabilized. In the present invention, the term "BET specific surface area" refers to a nitrogen adsorption specific surface area measured by the BET method.

[0029] In addition, it is preferable that the CNTs are not subjected to an aperture treatment, and that the t-plot obtained from the adsorption isotherm shows an upwardly convex shape. The "t-plot" can be obtained by converting the relative pressure into the average thickness t (nm) of the nitrogen gas adsorption layer in the adsorption isotherm of the CNTs measured by the nitrogen gas adsorption method. That is, the t-plot of the CNTs can be obtained by determining the average thickness t of the nitrogen gas adsorption layer corresponding to the relative pressure from a known standard isotherm in which the average thickness t of the nitrogen gas adsorption layer is plotted against the relative pressure P / P0, and performing the above conversion (t-plot method by de Boer et al.).

[0030] Here, in a material having pores on the surface, the growth of a nitrogen gas adsorption layer is classified into the following processes (1) to (3). The slope of the t-plot changes depending on the processes (1) to (3) below. (1) The process of forming a monolayer of nitrogen molecules on the entire surface (2) Formation of multilayer adsorption and the associated capillary condensation filling process in the pores (3) The formation of multilayer adsorption on an apparently non-porous surface whose pores are filled with nitrogen

[0031] In the t-plot showing an upward convex shape, the plot is located on a straight line passing through the origin in the region where the average thickness t of the nitrogen gas adsorption layer is small, whereas as t increases, the plot shifts downward from the straight line. CNTs having such a t-plot shape have a large ratio of the internal specific surface area to the total specific surface area of ​​the CNTs, indicating that many openings are formed in the CNTs.

[0032] The bending point of the t-plot of CNT is preferably in a range satisfying 0.2≦t(nm)≦1.5, more preferably in a range of 0.45≦t(nm)≦1.5, and particularly preferably in a range of 0.55≦t(nm)≦1.0. If the bending point of the t-plot of CNT is within such a range, the dispersibility of CNT can be improved, and the properties such as the conductivity of the conductive film can be improved with a small blending amount. Specifically, if the value of the bending point is less than 0.2, CNTs are likely to aggregate and the dispersibility is reduced, and if the value of the bending point is more than 1.5, CNTs are likely to be entangled with each other, and the dispersibility may be reduced. The "position of the bending point" is the intersection of the approximation line A in the above-mentioned process (1) and the approximation line B in the above-mentioned process (3).

[0033] Furthermore, the ratio (S2 / S1) of the internal specific surface area S2 to the total specific surface area S1 obtained from the t-plot of the CNTs is preferably 0.05 to 0.30. If the S2 / S1 value of the CNTs is within this range, the dispersibility of the CNTs can be increased, and the properties such as the conductivity of the conductive film can be improved with a small blending amount. Here, the total specific surface area S1 and the internal specific surface area S2 of the CNTs can be obtained from the t-plot. Specifically, first, the total specific surface area S1 can be obtained from the slope of the approximation line in step (1), and the external specific surface area S3 can be obtained from the slope of the approximation line in step (3). Then, the internal specific surface area S2 can be calculated by subtracting the external specific surface area S3 from the total specific surface area S1.

[0034] Incidentally, the measurement of the adsorption isotherm of CNT, the creation of t-plots, and the calculation of the total specific surface area S1 and the internal specific surface area S2 based on the analysis of the t-plots can be performed using, for example, a commercially available measuring device "BELSORP (registered trademark)-mini" (manufactured by BEL JAPAN, Inc.).

[0035] Furthermore, it is preferable that the CNTs have a radial breathing mode (RBM) peak when evaluated using Raman spectroscopy. Note that the Raman spectrum of three- or more-walled CNTs does not have an RBM.

[0036] Furthermore, the CNTs preferably have a ratio of G band peak intensity to D band peak intensity in a Raman spectrum (G / D ratio) of 0.5 to 10.0, more preferably 1.0 to 5.0. If the G / D ratio is 0.5 to 10.0, the resulting conductive film can be endowed with properties such as catalytic activity when used in a solar cell electrode.

[0037] Here, the CNTs preferably have an oxygen atomic content of 5 atomic % or less, more preferably 2 atomic % or less, and particularly preferably 1 atomic % or less, based on the total of carbon and oxygen atoms, as determined by elemental analysis using X-ray photoelectron spectroscopy (XPS). If the oxygen atomic content is within the preferred range, the resulting conductive film can be endowed with properties such as catalytic activity when used in solar cell electrodes.

[0038] The CNTs preferably have a carbon atom ratio of 85 mass% or more, more preferably 90 mass% or more, even more preferably 95 mass% or more, and particularly preferably 98 mass% or more, according to CHN elemental analysis, and the hydrogen atom ratio is preferably 1 mass% or less, more preferably 0.8 mass% or less, more preferably 0.3 mass% or less, and particularly preferably 0.1 mass% or less. If the ratio of carbon atoms and / or hydrogen atoms is within the preferred range, the obtained conductive film can be imparted with properties such as catalytic activity when used in a solar cell electrode.

[0039] In addition, CNTs can be produced by known CNT synthesis methods such as arc discharge, laser ablation, and chemical vapor deposition (CVD), without any particular limitation. Specifically, CNTs can be efficiently produced in accordance with a method (super growth method; see International Publication No. 2006 / 011655) in which, for example, a raw material compound and a carrier gas are supplied onto a substrate having a catalyst layer for CNT production on its surface, and a trace amount of an oxidizing agent (catalyst activation material) is made present in the system when synthesizing CNTs by chemical vapor deposition (CVD), dramatically improving the catalytic activity of the catalyst layer. In addition, hereinafter, carbon nanotubes obtained by the super growth method may be referred to as "SGCNTs". The CNT aggregate produced by the super-growth method may be composed of only SGCNTs, or may include, in addition to SGCNTs, other carbon nanostructures such as non-cylindrical carbon nanostructures.

[0040] The CNT content in the CNT aqueous dispersion is not particularly limited, but is preferably 0.001 mass% or more, more preferably 0.01 mass% or more, and even more preferably 0.1 mass% or more, and is preferably 30.0 mass% or less, more preferably 10.0 mass% or less, even more preferably 5.0 mass% or less, and particularly preferably 1.0 mass% or less, with the mass of the entire CNT aqueous dispersion being 100 mass%.

[0041] <Dispersant> The dispersant is not particularly limited as long as it is a compound that can disperse the above-mentioned CNTs in water and is soluble in the solvent (aprotic polar substance) in the electrolyte of the solar cell. Examples of aprotic polar substances used as a solvent for the electrolyte solution include five-membered cyclic carbonates such as ethylene carbonate and propylene carbonate (propylene carbonate); five-membered cyclic esters such as γ-butyrolactone and γ-valerolactone; aliphatic nitriles such as acetonitrile, 3-methoxypropionitrile, and methoxyacetonitrile; aliphatic chain ethers such as dimethoxyethane and triethylene glycol monomethyl ether; aliphatic cyclic ethers such as tetrahydrofuran and dioxane; aliphatic sulfones such as ethyl isopropyl sulfone; cyclic sulfones such as sulfolane; aliphatic sulfoxides such as dimethyl sulfoxide; dimethylformamide; and ethylmethylimidazolium bistrifluoromethylsulfonylimide. These may be used alone or in combination of two or more. Among these, acetonitrile, γ-butyrolactone, 3-methoxypropionitrile, and triethylene glycol monomethyl ether are preferred.

[0042] Examples of dispersants that are soluble in at least acetonitrile, γ-butyrolactone, and 3-methoxypropionitrile include copolymers of styrene and methoxypolyethylene glycol methacrylate, polyvinylpyrrolidone, polyoxyethylene alkyl ethers (the number of carbon atoms in the alkyl group is preferably 8 to 20), and polyoxyethylene alkylphenyl ethers (the number of carbon atoms in the alkyl group is preferably 8 to 9). Examples of dispersants that are soluble in at least triethylene glycol monomethyl ether include copolymers of styrene and methoxypolyethylene glycol methacrylate, and polyvinylpyrrolidone.

[0043] The dispersant may be used alone or in combination of two or more. From the viewpoint of further improving the film strength of the conductive film and further increasing the conversion efficiency and reliability of the solar cell, the dispersant is preferably a nonionic polymer, more preferably a copolymer of styrene and methoxypolyethyleneglycol methacrylate, or polyvinylpyrrolidone, and even more preferably a copolymer of styrene and methoxypolyethyleneglycol methacrylate. The content of the dispersant in the CNT aqueous dispersion is not particularly limited, but is preferably 50 parts by mass or more, more preferably 100 parts by mass or more, and preferably 500 parts by mass or less, and more preferably 300 parts by mass or less, per 100 parts by mass of the above-mentioned CNTs. If the content of the dispersant is within the above-mentioned range, the film strength of the conductive film can be further improved, while the conversion efficiency and reliability of the solar cell can be further increased.

[0044] In addition, in order to further improve the strength of the conductive film and to further increase the conversion efficiency and reliability of the solar cell, the copolymer of styrene and methoxypolyethylene glycol methacrylate is made by modifying the ethylene glycol chain portion of the repeating unit derived from methoxypolyethylene glycol methacrylate, "(CH 2 -CH 2 -O) n In the above formula, n (an integer) is preferably 1 or more and 20 or less, and more preferably 4 or more and 13 or less. In addition, the copolymer of styrene and methoxypolyethylene glycol methacrylate preferably has a weight average molecular weight of 10,000 or more and 30,000 or less, from the viewpoint of further improving the film strength of the conductive film while further increasing the conversion efficiency and reliability of the solar cell. In the present invention, the weight average molecular weight can be measured by gel permeation chromatography.

[0045] <Thickener> There are no particular limitations on the thickener, so long as it is a compound that can impart viscosity to the CNT aqueous dispersion and is insoluble in the solvent (aprotic polar substance) in the electrolyte of the solar cell.

[0046] Examples of thickeners that are insoluble at least in acetonitrile include cellulose-based polymers (hydroxyethyl cellulose, carboxymethyl cellulose, etc.) and polyvinyl alcohol. Examples of thickeners that are insoluble in at least γ-butyrolactone and 3-methoxypropionitrile include cellulose-based polymers (hydroxyethyl cellulose, carboxymethyl cellulose, etc.), polyethylene oxide, and polyvinyl alcohol. Examples of thickeners that are insoluble in at least triethylene glycol monomethyl ether include cellulose-based polymers (hydroxyethyl cellulose, carboxymethyl cellulose, etc.) and polyethylene oxide.

[0047] The thickener may be used alone or in combination of two or more. From the viewpoint of further improving the conversion efficiency of the solar cell, the thickener is preferably a nonionic polymer (polyethylene oxide, hydroxyethyl cellulose, etc.).

[0048] The content of the thickener in the CNT aqueous dispersion is not particularly limited, but is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and preferably 100 parts by mass or less, and more preferably 50 parts by mass or less, per 100 parts by mass of the above-mentioned CNTs. If the content of the thickener is within the above-mentioned range, the film strength of the conductive film can be further improved, while the conversion efficiency and reliability of the solar cell can be further increased.

[0049] <Solvent> As the solvent, at least water must be used, but a mixed solvent of water and a solvent miscible with water may be used. Examples of the solvent miscible with water include ethers (dioxane, tetrahydrofuran, methyl cellosolve, ethylene glycol dimethyl ether, ethylene glycol butyl ether, etc.), ether alcohols (ethoxyethanol, methoxyethoxyethanol, etc.), esters (methyl acetate, ethyl acetate, etc.), ketones (acetone, methyl isobutyl ketone, cyclohexanone, methyl ethyl ketone, etc.), alcohols (methanol, ethanol, isopropanol, propylene glycol, ethylene glycol, diacetone alcohol, phenol, etc.), lower carboxylic acids (acetic acid, etc.), amines (triethylamine, trimethanolamine, etc.), nitrogen-containing polar solvents (N,N-dimethylformamide, nitromethane, N-methylpyrrolidone, acetonitrile, etc.), and sulfur compounds (dimethyl sulfoxide, etc.). These may be used alone or in combination of two or more.

[0050] <Other ingredients> Other components include inorganic substances such as silica, metal particles, binders, conductive assistants, surfactants, defoamers, antioxidants, preservatives, etc. Known substances may be used as appropriate. These may be used alone or in combination of two or more.

[0051] <Preparation method> The method for preparing the CNT aqueous dispersion is not particularly limited, and for example, the CNT aqueous dispersion can be obtained by subjecting CNT, a dispersant, a thickener, and other components used as necessary to a known mixing and dispersion treatment in the presence of a solvent containing water. Examples of known mixing and dispersion treatments include methods using wet jet mills such as Nanomizer and Ultimizer, high-pressure homogenizers, ultrasonic dispersers, ball mills, sand grinders, Dyno Mills, spike mills, DCP mills, basket mills, paint conditioners, and high-speed stirring devices such as homomixers. The temperature during the mixing and dispersion treatment is not particularly limited, but is usually equal to or lower than the boiling point of the water-containing solvent, and is preferably equal to or lower than 60° C., more preferably equal to or lower than 40° C., and is preferably equal to or higher than −10° C., and more preferably equal to or higher than 0° C. If the temperature is within this range, the solubility and structure of the dispersant can be controlled, and the dispersibility of the CNTs can be improved.

[0052] The pH of the CNT aqueous dispersion is not particularly limited, but is preferably 0.1 or more, more preferably 0.2 or more, and particularly preferably 0.5 or more, and is preferably less than 7 (i.e., acidic), more preferably 6 or less, even more preferably 5 or less, even more preferably 4 or less, and particularly preferably 2.5 or less. By setting the pH of the CNT aqueous dispersion within the above range, the stability of the CNT aqueous dispersion can be ensured. To lower the pH of the CNT aqueous dispersion, an acidic substance such as sulfuric acid, hydrochloric acid, nitric acid, citric acid, oxalic acid, tartaric acid, formic acid, or phosphoric acid may be added.

[0053] (Conductive film) The conductive film of the present invention is formed by using the above-mentioned CNT aqueous dispersion of the present invention. Since the conductive film of the present invention is formed from the CNT aqueous dispersion of the present invention, it has excellent film strength. The conductive film of the present invention can be suitably used as a member constituting the electrodes (photoelectrode, counter electrode) of a solar cell.

[0054] <Properties> The thickness of the conductive film of the present invention is not particularly limited, but is usually 100 nm or more and 1 mm or less. When used as an electrode for a solar cell (particularly a dye-sensitized solar cell), the thickness of the conductive film is preferably 0.01 μm or more and 100 μm or less, more preferably 0.1 μm or more and 20 μm or less, and even more preferably 0.5 μm or more and 10 μm or less. If the thickness of the conductive film is within the above-mentioned range, the conductive film has excellent conductivity and catalytic performance as an electrode, and when made into a module, the conductive film has an excellent balance of the overall series resistance, etc.

[0055] In addition, the surface resistivity of the conductive film of the present invention is not particularly limited, but is, for example, 0.01 Ω / □ or more and 1000 Ω / □ or less, preferably 0.1 Ω / □ or more and 100 Ω / □ or less, and more preferably 0.5 Ω / □ or more and 20 Ω / □ or less. The surface resistivity of the conductive film can be measured using a low resistivity meter (for example, product name "Loresta (registered trademark)-GP MCP-T610" manufactured by Mitsubishi Chemical Analytech Corporation) according to a method in accordance with JIS K7194.

[0056] <Manufacturing method> The method for producing the conductive film of the present invention is not particularly limited as long as it is a method using the above-mentioned CNT aqueous dispersion of the present invention. The conductive film of the present invention can be produced, for example, through a step of coating the CNT aqueous dispersion on a substrate (coating step) and a step of drying the CNT aqueous dispersion on the substrate (drying step). The production method may include steps (other steps) other than the coating step and the drying step.

[0057] <Coating process> In the coating step, the above-mentioned CNT aqueous dispersion of the present invention is coated onto a substrate.

[0058] Here, the substrate is not particularly limited in shape, constituent material, and size (thickness, etc.) as long as it can be coated with the above-mentioned CNT aqueous dispersion and can support the obtained conductive film, and can be appropriately selected depending on the intended application, but it is preferable to use a support used for the electrode of the present invention described below.

[0059] As a method for applying the CNT aqueous dispersion onto the substrate, a known application method can be used. Examples of the coating method include dipping, roll coating, gravure coating, knife coating, air knife coating, roll knife coating, die coating, screen printing, spray coating, gravure offset, ink jet, spraying, etc. Among these, screen printing is preferred. Moreover, the coating may be carried out not only once but also several times as necessary, and two different coating methods may be combined.

[0060] The coating thickness (wet thickness) when the CNT aqueous dispersion is applied to a substrate is not particularly limited as long as the conductivity of the resulting conductive film is ensured; however, it is preferably 0.001 μm or more, more preferably 0.005 μm or more, and particularly preferably 0.01 μm or more, and is preferably 500 μm or less, more preferably 300 μm or less, and particularly preferably 200 μm or less. In addition, when the CNT aqueous dispersion is applied to the substrate, the amount of CNT applied per unit area of ​​the substrate is 0.001 mg / m 2 It is preferable that the concentration is 0.005 mg / m or more. 2 More preferably, it is 0.01 mg / m or more. 2 It is particularly preferable that the content is 50 g / m or more. 2 It is preferable that the thickness is less than 10 g / m 2 More preferably, it is 3 g / m or less. 2 It is particularly preferred that:

[0061] <Drying process> In the drying step, the coating film of the CNT aqueous dispersion formed on the substrate in the coating step is dried to obtain a laminate including the substrate and a dried film of the CNT aqueous dispersion.

[0062] Here, the method for drying the CNT aqueous dispersion on the substrate is not particularly limited, and any known drying method can be used. Examples of such drying methods include air drying, heat drying such as hot roll drying, reduced pressure drying, infrared irradiation, light irradiation using a xenon lamp or flash lamp, and electromagnetic wave heating such as microwaves. The drying temperature is not particularly limited as long as the solvent including water can be removed by evaporation and the substrate is not deformed. The drying temperature is preferably 0°C or higher, more preferably 15°C or higher, even more preferably 25°C or higher, particularly preferably 80°C or higher, preferably 250°C or lower, more preferably 200°C or lower, and particularly preferably 150°C or lower. The drying time is not particularly limited, but is preferably 0.1 minute or more and 150 minutes or less. The drying atmosphere is not particularly limited, and may be a humidified atmosphere, air, an inert gas such as nitrogen or argon, or a reduced pressure such as vacuum.

[0063] <Other processes> The other steps are not particularly limited, but include a step of washing the dried film of the CNT aqueous dispersion obtained through the above-mentioned drying step with a washing solvent (washing step). That is, the dried film of the CNT aqueous dispersion obtained through the above-mentioned drying step can be used as it is as the conductive film of the present invention, or the dried film further subjected to a washing step can be used as the conductive film of the present invention.

[0064] By carrying out the washing step, it is possible to remove at least a part of the dispersant contained in the dried film of the CNT aqueous dispersion. The washing solvent used in the washing step is not particularly limited as long as it is a washing solvent that can remove the dispersant by contacting with the dried film, and water can also be used. However, in the present invention, it is preferable to produce the conductive film without performing a washing step with water. This is because there is a risk that not only the dispersant but also the thickener will be removed by performing a washing step with water. In order to remove the dispersant while leaving the thickener, it is preferable to use the above-mentioned aprotic polar substance as a washing solvent in the washing step, and it is more preferable to use at least one of acetonitrile, γ-butyrolactone, 3-methoxypropionitrile, and triethylene glycol monomethyl ether, and it is particularly preferable to use acetonitrile from the viewpoint of ease of removing the dispersant. The washing solvent may be used alone or in combination of two or more kinds.

[0065] The washing method is not particularly limited as long as it is a method that can bring the above-mentioned washing solvent into contact with the conductive film, and can be performed using a known method such as coating, immersion, etc. The washing may be performed multiple times. After washing, drying can be performed using a known method.

[0066] (electrode) The electrode of the present invention includes the conductive film of the present invention described above. Since the electrode of the present invention includes the conductive film of the present invention, the electrode can ensure the reliability of the solar cell while allowing the solar cell to exhibit excellent conversion efficiency. The electrode of the present invention is suitably used as an electrode (photoelectrode, counter electrode) of a dye-sensitized solar cell, particularly as a counter electrode of a dye-sensitized solar cell.

[0067] Hereinafter, the electrode of the present invention will be described using an example in which the electrode is a counter electrode of a dye-sensitized solar cell and the counter electrode has the conductive film of the present invention as a catalyst layer, but the present invention is not limited thereto.

[0068] <Counter electrode> The counter electrode is an electrode for efficiently transferring electrons that have entered from an external circuit to the electrolyte layer. The counter electrode includes, for example, a support, a conductive layer provided on the support, and a catalyst layer provided on the conductive layer. In a preferred embodiment of the present invention, the conductive film of the present invention is used as the catalyst layer of the counter electrode, as described above.

[0069] <<Support>> A known support can be used as the support of the counter electrode. Specifically, a support made of a transparent resin or a support made of glass can be used as the support of the counter electrode, and it is particularly preferable to use a support made of a transparent resin. Examples of transparent resins include synthetic resins such as cycloolefin polymer (COP), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), syndiotactic polystyrene (SPS), polyphenylene sulfide (PPS), polycarbonate (PC), polyarylate (PAr), polysulfone (PSF), polyester sulfone (PES), polyetherimide (PEI), and transparent polyimide (PI).

[0070] <<Conductive layer and catalyst layer>> The conductive layer of the counter electrode can be a known conductive film. Examples of known conductive films include conductive films made of oxides such as indium tin oxide (ITO) and indium zinc oxide (IZO), conductive films made of conductive polymers such as polythiophenes and polyanilines, such as PEDOT [poly(3,4-ethylenedioxythiophene)] / PSS (polystyrene sulfonate), and conductive films containing conductive carbon such as natural graphite, activated carbon, artificial graphite, graphene, and CNT (excluding the conductive film of the present invention).

[0071] As the catalyst layer of the counter electrode, it is preferable to use the conductive membrane of the present invention as described above.

[0072] The method for forming the conductive layer and the catalyst layer is not particularly limited, and known methods can be used. For example, when the conductive film of the present invention is used as the catalyst layer, the CNT aqueous dispersion of the present invention is applied onto a support having a conductive layer such as an ITO film (on the ITO film), and then dried, so that the support, the conductive layer (ITO film), and the catalyst layer can be laminated in this order.

[0073] (Solar Cell) The solar cell of the present invention includes the electrode of the present invention described above. Since the solar cell of the present invention includes the electrode of the present invention described above, it has excellent conversion efficiency and reliability. The solar cell of the present invention is preferably a dye-sensitized solar cell.

[0074] The solar cell of the present invention will be described below by taking as an example a case where the solar cell is a dye-sensitized solar cell, but the present invention is not limited thereto.

[0075] As shown in FIG. 1, the dye-sensitized solar cell 100 according to the present invention has a photoelectrode 10, an electrolyte layer 20, and a counter electrode 30, and the electrolyte layer 20 is located between the photoelectrode 10 and the counter electrode 30. The photoelectrode 10 includes a support 10a, a conductive layer 10b provided on the support 10a, a porous semiconductor fine particle layer 10c made of semiconductor fine particles, and a sensitizing dye layer 10d made of a sensitizing dye adsorbed on the surface of the semiconductor fine particles in the porous semiconductor fine particle layer 10c, and the porous semiconductor fine particle layer 10c and the sensitizing dye layer 10d are formed on the conductive layer 10b. The counter electrode 30 includes a support 30a, a conductive layer 30b provided on the support 30a, and a catalyst layer 30c provided on the conductive layer 30b. The conductive layer 10b of the photoelectrode 10 and the conductive layer 30b of the counter electrode 30 are connected via an external circuit 40.

[0076] <Photoelectrode and counter electrode> A dye-sensitized solar cell as a solar cell of the present invention includes the above-mentioned electrode of the present invention as at least one of the photoelectrode 10 and the counter electrode 30. The dye-sensitized solar cell preferably includes the conductive film of the present invention as the catalyst layer 30c of the counter electrode 30 as described above.

[0077] The photoelectrode 10 is an electrode that can emit electrons to an external circuit by receiving light. As described above, the photoelectrode 10 includes, for example, a support 10a, a conductive layer 10b provided on the support, a porous semiconductor fine particle layer 10c made of semiconductor fine particles, and a sensitizing dye layer 10d made of a sensitizing dye adsorbed on the surfaces of the semiconductor fine particles in the porous semiconductor fine particle layer.

[0078] The support 10a and conductive layer 10b of the photoelectrode may both be known materials. Specifically, the support 10a of the photoelectrode may be the same as that described above as the "support of the counter electrode," and the conductive layer 10b of the photoelectrode may be the same as that described above as the "conductive layer of the counter electrode."

[0079] The porous semiconductor fine particle layer 10c of the photoelectrode can be formed using particles (semiconductor fine particles) of metal oxides such as titanium oxide, zinc oxide, tin oxide, etc. The metal oxide particles may be used alone or in combination of two or more kinds. The porous semiconductor fine particle layer 10c can be formed by a pressing method, a hydrothermal decomposition method, a migration electrodeposition method, a binder-free coating method, or the like.

[0080] Further, examples of sensitizing dyes that are adsorbed to the surfaces of the semiconductor particles in the porous semiconductor particle layer 10c to form the sensitizing dye layer 10d include organic dyes such as cyanine dyes, merocyanine dyes, oxonol dyes, xanthene dyes, squarylium dyes, polymethine dyes, coumarin dyes, riboflavin dyes, and perylene dyes; metal complex dyes such as phthalocyanine complexes and porphyrin complexes of metals such as iron, copper, and ruthenium; etc. The sensitizing dyes may be used alone or in combination of two or more. The sensitizing dye layer 10d can be formed, for example, by immersing the porous semiconductor fine particle layer 10c in a solution of the sensitizing dye or by applying the solution of the sensitizing dye onto the porous semiconductor fine particle layer 10c.

[0081] <Electrolyte layer> The electrolyte layer 20 usually contains a supporting electrolyte, a redox pair (a pair of chemical species that can be reversibly converted into an oxidant and a reductant in an oxidation-reduction reaction), a solvent, and the like.

[0082] Here, examples of the supporting electrolyte include salts containing cations such as lithium ions, imidazolium ions, quaternary ammonium ions, etc. These may be used alone or in combination of two or more. As the redox couple, as long as it can reduce the oxidized sensitizing dye, examples thereof include chlorine compound-chlorine, iodine compound-iodine, bromine compound-bromine, thallium ion (III)-thallium ion (I), ruthenium ion (III)-ruthenium ion (II), copper ion (II)-copper ion (I), iron ion (III)-iron ion (II), cobalt ion (III)-cobalt ion (II), vanadium ion (III)-vanadium ion (II), manganate ion-permanganate ion, ferricyanide-ferrocyanide, quinone-hydroquinone, fumaric acid-succinic acid, etc. These may be used alone or in combination of two or more. Furthermore, the above-mentioned aprotic polar substances can be used as the solvent. These may be used alone or in combination of two or more.

[0083] The electrolyte layer 20 can be formed by applying a solution (electrolyte solution) containing its constituent components onto the photoelectrode 10, or by preparing a cell having the photoelectrode 10 and the counter electrode 30 and injecting the electrolyte solution into the gap between them.

[0084] (Solar cell module) The above-mentioned solar cells of the present invention can be connected in series and / or parallel to form a solar cell module. Here, the solar cell module can be obtained, for example, by arranging the solar cells of the present invention on a flat or curved surface, providing non-conductive partition walls between each cell, and electrically connecting the photoelectrodes and counter electrodes of each cell using conductive members. Furthermore, a solar cell module including the solar cell of the present invention has excellent conversion efficiency and reliability. The number of solar cells used to form the solar cell module is not particularly limited, and can be appropriately determined depending on the target voltage. EXAMPLES

[0085] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples. In the following description, "%" and "parts" expressing amounts are based on mass unless otherwise specified. Evaluations in the present examples were performed by the following methods.

[0086] <Appearance of conductive film (film strength)> For the conductive film of the counter electrode (PEN + ITO film + conductive film), any 1 cm 2 The area was visually inspected to check for pinholes of 1 mm or less in diameter and for peeling of the conductive film (lifting from the ITO film). Evaluation was then performed according to the following criteria. A: Neither pinholes nor peeling occurred. B: Pinholes occurred, but no peeling occurred C: Peeling occurred <Solar cell conversion efficiency> The light source used was a simulated solar irradiation device (PEC-L11, manufactured by Peccel Technologies) equipped with a 150 W xenon lamp light source and an AM1.5G filter. The light intensity was 1 sun (AM1.5G, 100 mW / cm2). 2 (Class A of JIS C8912). The fabricated solar cell was connected to a source meter (2400 type source meter, manufactured by Keithley Instruments) and the following current-voltage characteristics were measured. Under 1 sun of light irradiation, the output current was measured while changing the bias voltage from 0 V to 0.8 V in 0.01 V increments. The output current was measured by integrating the value from 0.05 seconds to 0.15 seconds after changing the voltage at each voltage step. Measurements were also performed while changing the bias voltage in the reverse direction from 0.8 V to 0 V, and the average value of the measurements in the forward and reverse directions was taken as the photocurrent. The conversion efficiency (%) was calculated from the measurement results of the current-voltage characteristics and evaluated according to the following criteria. A: Conversion efficiency is 4.0% or more B: Conversion efficiency is 3.5% or more and less than 4.0% C: Conversion efficiency is less than 3.5% <Reliability of Solar Cells> The fabricated solar cell was placed in an aluminum bag for gas barrier and left in a thermo-hygrostat (60 °C) for 500 hours. Then, for the solar cell after the leaving, the conversion efficiency (%) was calculated in the same manner as above and evaluated according to the following criteria. A: Conversion efficiency after 500 hours of leaving is 3.5% or more B: Conversion efficiency after 500 hours of leaving is 3.0% or more and less than 3.5% C: Conversion efficiency after 500 hours of leaving is less than 3.0%

[0087] (Example 1) <Preparation of CNT Aqueous Dispersion> Into a 500 mL polyvinyl bottle, 2.0 g of single-walled CNT (manufactured by Nippon Zeon Co., Ltd., product name "SG101"), 6.0 g (300 parts per 100 parts of single-walled CNT) of a copolymer of styrene and methoxypolyethylene glycol methacrylate (manufactured by Kusumoto Chemical Co., Ltd., product name "Disparlon (registered trademark) AQ-380", soluble in acetonitrile, weight average molecular weight 15,000, ethylene glycol chain part "(CH 2 -CH 2 -O) n )" with n = 9) as a pure component, 1.0 g (50 parts per 100 parts of single-walled CNT) of hydroxyethyl cellulose (manufactured by Daicel Finechem Co., Ltd., product name "SP600", insoluble in acetonitrile) as a thickener, and 400 g of pure water were added to obtain a mixture. The obtained mixture was stirred with a homomixer at 6000 rpm for 30 minutes while cooling the polyvinyl bottle to 25 °C in a water bath to obtain a coarse dispersion. The obtained coarse dispersion was treated with a wet jet mill (manufactured by Yoshida Kikai Kogyo Co., Ltd., product name "Nanovator (registered trademark)") at 100 MPa for 10 passes while cooling the dispersion to 25 °C to obtain a CNT aqueous dispersion. <Fabrication of Counter Electrode> The CNT aqueous dispersion prepared as described above was applied to an ITO-PEN film (50 mm x 50 mm, 15 Ω / □) by screen printing using a 100 mesh screen, and dried in an inert oven (manufactured by Yamato Scientific Co., Ltd.) in air at 125°C for 15 minutes to form a coating film. This coating film was dried at 60°C under reduced pressure for 2 hours to prepare a counter electrode having a support made of polyethylene naphthalate, an ITO film as a conductive layer, and the conductive film of the present invention as a catalyst layer in this order. The appearance (film strength) of the conductive film was evaluated using this counter electrode. The results are shown in Table 1. <Fabrication of photoelectrode> A ruthenium complex (manufactured by Solaronics: product name N719) was used as the sensitizing dye, and a sensitizing dye solution (concentration: 0.3 mM) was prepared using ethanol as the solvent. A 5 mM titanium isopropoxide solution in isopropyl alcohol was applied onto an ITO-PEN film (50 mm x 50 mm, 15 Ω / □) by bar coating, and dried in an inert oven (Yamato Scientific Co., Ltd.) at 150 °C for 15 minutes. A thermosetting Ag paste (Toyochem Co., Ltd.) was printed using a screen printer (SFA-PC610CTN, made by ceria) and heated in an inert oven (Yamato Scientific Co., Ltd.) at 130 °C for 30 minutes to form an extraction electrode (thickness 8 μm). Furthermore, a water-based titanium oxide paste (PECC-AW1-01, made by Pexel Technologies Co., Ltd.) was applied using a screen printer and dried in an inert oven (Yamato Scientific Co., Ltd.) at 150 °C for 15 minutes to form a porous semiconductor layer (the thickness of the titanium oxide layer was 8 μm). The ITO-PEN film on which the porous semiconductor layer was formed was placed in the sensitizing dye solution (50 cm tub) prepared as described above and immersed for 2 hours at 40° C. After immersion, it was washed with an ethanol solution and dried under reduced pressure at 40° C. for 24 hours to prepare a photoelectrode. <Solar cell manufacturing> An electrolyte solution was obtained by dissolving iodine 0.05 mol / L, lithium iodide 0.1 mol / L, t-butylpyridine 0.5 mol / L, and 1,2-dimethyl-3-propylimidazolium iodide 0.6 mol / L in acetonitrile as a solvent. In a vacuum lamination device, a sealant (polybutylene-based photocurable resin and 8% by mass of 25 μm insulating spacer resin) was applied to the photoelectrode with a dispenser so that the sealant width after lamination was 0.9 mm and the height was 30 μm, and then the electrolyte solution obtained as described above was applied to the photoelectrode. The counter electrode was placed in the vacuum lamination device, and the electrodes were laminated in a vacuum, and UV irradiation was performed using a metal halide lamp with an integrated light amount of 3000 mJ / cm. 2 The sealing material was cured by heating at 40° C., and the substrates were laminated together. The vacuum was released to atmospheric pressure to produce a dye-sensitized solar cell as a solar cell. The conversion efficiency and reliability of this solar cell were evaluated. The results are shown in Table 1.

[0088] Example 2 In preparing the CNT aqueous dispersion, except that polyvinylpyrrolidone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., product name "Polyvinylpyrrolidone K30", soluble in acetonitrile) was used as the dispersant instead of the copolymer of styrene and methoxypolyethylene glycol methacrylate, the CNT aqueous dispersion, counter electrode, photoelectrode, and solar cell were prepared and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0089] Example 3 In preparing the CNT aqueous dispersion, except that carboxymethyl cellulose (manufactured by Daicel FineChem, product name "CMC1380", insoluble in acetonitrile) was used as the thickener instead of hydroxyethyl cellulose, the CNT aqueous dispersion, counter electrode, photoelectrode, and solar cell were prepared and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0090] Example 4 In producing the solar cell, except that γ-butyrolactone was used instead of acetonitrile as the solvent for the electrolyte, a CNT aqueous dispersion, a counter electrode, a photoelectrode, and a solar cell were prepared and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1. The dispersant, a copolymer of styrene and methoxypolyethylene glycol methacrylate, was soluble in γ-butyrolactone, while the thickener, hydroxyethyl cellulose, was insoluble in γ-butyrolactone.

[0091] Example 5 In preparing the CNT aqueous dispersion, a CNT aqueous dispersion, a counter electrode, a photoelectrode, and a solar cell were prepared and various evaluations were performed in the same manner as in Example 4, except that polyethylene oxide (manufactured by Sumitomo Seika Chemicals, product name "PEO-8", insoluble in γ-butyrolactone) was used as a thickener instead of hydroxyethyl cellulose. The results are shown in Table 1.

[0092] Example 6 In producing the solar cell, except that 3-methoxypropionitrile was used instead of acetonitrile as the solvent for the electrolyte, a CNT aqueous dispersion, a counter electrode, a photoelectrode, and a solar cell were prepared and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1. The dispersant, a copolymer of styrene and methoxypolyethylene glycol methacrylate, was soluble in 3-methoxypropionitrile, while the thickener, hydroxyethyl cellulose, was insoluble in 3-methoxypropionitrile.

[0093] Example 7 In producing the solar cell, except that triethylene glycol monomethyl ether was used instead of acetonitrile as the solvent for the electrolyte, a CNT aqueous dispersion, a counter electrode, a photoelectrode, and a solar cell were prepared and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1. The dispersant, a copolymer of styrene and methoxypolyethylene glycol methacrylate, was soluble in triethylene glycol monomethyl ether, while the thickener, hydroxyethyl cellulose, was insoluble in triethylene glycol monomethyl ether.

[0094] Comparative Example 1 In preparing the CNT aqueous dispersion, polystyrene sodium sulfonate (manufactured by Sigma-Aldrich, product name "Poly(sodium 4-styrenesulfonate)", insoluble in acetonitrile) was used as the dispersant instead of the copolymer of styrene and methoxypolyethylene glycol methacrylate, and hydroxyethyl cellulose was not used as the thickener, but the CNT aqueous dispersion, counter electrode, photoelectrode, and solar cell were prepared and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0095] Comparative Example 2 In preparing the CNT aqueous dispersion, sodium polyacrylate (Sigma-Aldrich, insoluble in acetonitrile) was used as the dispersant instead of the copolymer of styrene and methoxypolyethylene glycol methacrylate, and hydroxyethyl cellulose was not used as the thickener, but the CNT aqueous dispersion, counter electrode, photoelectrode, and solar cell were prepared and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0096] Comparative Example 3 A photoelectrode and a solar cell were prepared in the same manner as in Comparative Example 1, except that the counter electrode was prepared as follows, and various evaluations were carried out. The results are shown in Table 2. <Preparation of counter electrode> The counter electrode obtained in the same manner as in Comparative Example 1 was further immersed in ion-exchanged water for 30 minutes and dried in an inert oven (manufactured by Yamato Scientific Co., Ltd.) at 125°C in an air atmosphere for 15 minutes to obtain a counter electrode used in Comparative Example 3.

[0097] Comparative Example 4 Except for not using hydroxyethyl cellulose as a thickener in preparing the CNT aqueous dispersion, the CNT aqueous dispersion, the counter electrode, the photoelectrode, and the solar cell were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0098] Comparative Example 5 In preparing the CNT aqueous dispersion, except that polyethylene oxide (manufactured by Sumitomo Seika Chemicals, product name "PEO-8", soluble in acetonitrile) was used as the thickener instead of hydroxyethyl cellulose, the CNT aqueous dispersion, counter electrode, photoelectrode, and solar cell were prepared and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0099] In addition, in Tables 1 and 2 shown below, "AQ380" refers to a copolymer of styrene and methoxypolyethylene glycol methacrylate. "PVP" refers to polyvinylpyrrolidone; "SPS" stands for sodium polystyrene sulfonate; "SPA" stands for sodium polyacrylate; "HEC" stands for hydroxyethyl cellulose; "CMC" stands for carboxymethyl cellulose; "PEO" stands for polyethylene oxide. "γ-BL" indicates γ-butyrolactone; "3-MPN" refers to 3-methoxypropionitrile; "TGME" refers to triethylene glycol monomethyl ether.

[0100] [Table 1]

[0101] [Table 2]

[0102] It can be seen from Tables 1 and 2 that by using the CNT aqueous dispersions of Examples 1 to 7, a conductive film with excellent film strength, and a solar cell with excellent conversion efficiency and reliability can be produced. [Industrial Applicability]

[0103] According to the present invention, it is possible to provide an aqueous dispersion of carbon nanotubes capable of forming a conductive film having excellent film strength and capable of enabling a solar cell to exhibit excellent conversion efficiency and reliability. Furthermore, according to the present invention, it is possible to provide a conductive film that has excellent film strength and is capable of enabling a solar cell to exhibit excellent conversion efficiency and reliability. Furthermore, according to the present invention, it is possible to provide an electrode that can ensure the reliability of a solar cell while allowing the solar cell to exhibit excellent conversion efficiency. Furthermore, according to the present invention, it is possible to provide a solar cell having excellent conversion efficiency and reliability. [Explanation of symbols]

[0104] 10 Photoelectrode 30 Counter electrode 20 Electrolyte layer 10a,30a Support 10b,30b conductive layer 10c Porous semiconductor particle layer 10d Sensitizing dye layer 30c catalyst layer 40 Circuits 100 Dye-sensitized solar cell

Claims

1. A carbon nanotube aqueous dispersion for a solar cell electrode, comprising an electrolyte solution containing an aprotic polar substance as a solvent, The present invention relates to a composition comprising carbon nanotubes, a dispersant, a thickener, and water, the dispersant is soluble in the solvent and the thickener is insoluble in the solvent; The carbon nanotube aqueous dispersion has a content of the dispersant of 50 parts by mass or more and 500 parts by mass or less per 100 parts by mass of the carbon nanotubes, and a content of the thickener of 5 parts by mass or more and 100 parts by mass or less per 100 parts by mass of the carbon nanotubes.

2. 2. The carbon nanotube aqueous dispersion according to claim 1, wherein the aprotic polar substance is at least one selected from the group consisting of acetonitrile, γ-butyrolactone, 3-methoxypropionitrile, and triethylene glycol monomethyl ether.

3. The carbon nanotube aqueous dispersion according to claim 1 or 2, wherein the dispersant and the thickener each comprise a non-ionic polymer.

4. 4. The carbon nanotube aqueous dispersion according to claim 1, wherein the dispersant is a copolymer of styrene and methoxypolyethylene glycol methacrylate.

5. A conductive film obtained by using the carbon nanotube aqueous dispersion according to any one of claims 1 to 4.

6. An electrode comprising the conductive film according to claim 5 .

7. A solar cell comprising the electrode according to claim 6.

Citation Information

Patent Citations

  • Photoelectric conversion element and method of manufacturing the same

    JP2011014411A

  • Carbon nanotube production method

    JP2012066953A

  • Method of manufacturing carbon counter electrode for dye-sensitized solar cell

    JP2014063678A

  • Electrode substrate for solar cell

    JP2015128099A

  • Method for manufacturing conductivity laminate, conductivity laminate, counter electrode for dye-sensitized solar batteries, dye-sensitized solar battery, and solar battery module

    JP2015146338A